Strategi Kebijakan Konservasi Hutan Tropis Indonesia Untuk Mengatasi Perubahan Iklim: Sebuah Literatur Review - Anto Anto; Fatmawati Andi Mappasere; Jaelan Usman; Alyas Alyas (Jurnal Ilmu Sosial dan Ilmu Politik)
Climate change is a significant global issue, with deforestation and forest degradation contributing substantially to greenhouse gas emissions. This study aims to analyze the status of forest areas in Indonesia, identify the impact of deforestation and forest degradation on climate change, and evaluate the effectiveness of the REDD+ strategy as a conservation effort to address climate change. The research method used is a systematic literature review, involving the identification, screening, and analysis of data from various scientific sources. The results indicate that Indonesia has 120.5 million hectares of forest area; however, the high rate of deforestation is driven by land conversion for plantations, illegal logging, and mining activities. This deforestation contributes to increased CO2 emissions and exacerbates climate change. The implementation of the REDD+ strategy in Indonesia has shown potential in reducing the rate of deforestation and forest degradation through economic incentives and the enhancement of local capacity. This study highlights the importance of sustainable forest management and effective REDD+ policy implementation to address climate change.